The opportunities and challenges to be a shariah compliant hotel: A case of LKPP De Rhu Beach Resort / Siti Aishah Mohamad …[et al.] - Mohamad, Siti Aishah; Yahya, Wan Kalthom; Azer, Ilyani; Che Hamzah, Hamnah (2013)
Shariah compliant hotel can be defined as a hotel that provides services in accordance to the Shariah principles. The Shariah compliant hotel is not only limited to serve halal food and drink but the operation throughout the hotel would also be managed based on Shariah principles. The increasing numbers of international visitors from Islamic countries particularly from Middle East create a bright prospect for tourism industry because of the Islamic identity of Malaysia and Muslim friendly services offered LKPP DE RHU Beach resort is the only one resort hotel in Pahang that has been certified halal by JAKIM for the whole operation. It had stopped selling and serving liquor to guests since 2003. However, to be shariah compliant hotel, there are requirements in terms of financial and operations aspects to be met. Therefore, the aims of this paper are to find the opportunities and challenges of LKPP De Rhu Beach Resort to be fully shariah compliant hotel. The findings can be used by LKPP De Rhu Beach Resort to make improvemen.t to be the shariah compliant hotel.